Unveiling ancient diversity of long-tailed wasps (Hymenoptera: Megalyridae): new taxa from Cretaceous Kachin and Taimyr ambers and their phylogenetic affinities - Brazidec,Manuel; Vilhelmsen,Lars; Boudinot,Brendon; Richter,Adrian; Hammel,Jörg U.; Perkovsky,Evgeny; Fan,Yong; Wang,Zhen; Wu,Qiong; Wang,Bo; Perrichot,Vincent (Arthropod Systematics & Phylogeny, 2024)
The Megalyridae are a small family of parasitoid wasps comprising eight extant genera (71 species) and six extinct genera (13 species). Here, we report eight new species from Late Cretaceous Kachin (Myanmar) and Taimyr (Russia) ambers; the family is recorded for the first time from the latter. †Cretolyra noijebumensis gen. et sp. nov., †Cretolyra shawi gen. et sp. nov., †Genkyhag innebula gen. et sp. nov., †Megacoxa chandrahrasa gen. et sp. nov., †Megacoxa janzeni gen. et sp. nov., and †Megacoxa synchrotron gen. et sp. nov., are described from late Albian – early Cenomanian Kachin amber; †Kamyristi exfrigore gen. et sp. nov. and †Kamyristi yantardakhensis gen. et sp. nov. from Taimyr amber (Baikura, late Albian – early Cenomanian Ognevka Formation and Yantardakh, Santonian Kheta Formation, respectively). Phylogenetic analyses of the family are presented and the classification of the Megalyridae is revised accordingly. A new tribe, †Megalavini trib. nov., is erected to accommodate †Cretolyra gen. nov., †Genkyhag gen. nov., †Megacoxa gen. nov. together with †Megalava Perrichot, 2009; †Megalavini trib. nov. is characterized by the vein M fully pigmented and veins Rs+M and M+Cu aligned, the crenulate mesometapectal sulcus, and the pronotal spiracle not posteriorly surrounded by cuticle. This spiracular condition was previously only observed in †Megazar Perrichot, 2009, thus the subfamily †Megazarinae Perrichot, 2009 stat. nov. is proposed for the clade (†Megalavini + †Megazar), as sister to the remaining Megalyridae. The latter is defined as the Megalyrinae, with †Kamyristi gen. nov. being retrieved as sister to all other genera except Rigel Shaw, 1987 under parsimony analyses. To align phylogeny with classification, three new tribes are erected (†Kamyristini trib. nov., †Megallicini trib. nov., and †Valaaini trib. nov.) and the †Cretodinapsini is synonymized under Megalyrini. A grouping [Rigel + Megalyridia] is supported under Bayesian analyses, which is the only specific conflict with the parsimony analyses, ...